Bauran Pemasaran Kafe K2B Kelurahan Kleak Kota Manado - Labia, Serlianti; Rori, Yolanda Pinky Ivanna; Pangemanan, Lyndon Reindhardt Jacob (Sam Ratulangi University, 2023)
This study aims to identify and analyze the marketing mix at K2B cafes in Kleak Village, Manado City. This research was conducted from August to September 2022. The selection of respondents was carried out by chance, that is, with whom the respondent met the researcher. The data used are primary data and secondary data. Primary data was obtained from K2B internet cafe owners in Kleak Village, Manado City. Secondary data was collected through interviews, based on a questionnaire, so that a total of 20 respondents. The results showed that there were 2 marketing mix variables that were satisfied, namely product variables (81.10%) and price (84.44%) while those who felt dissatisfied were place and promotion variables.